(untitled) - Langan, John (New York, 2005)
This text is intended for composition courses designed to help students master the five-paragraph essay. It focuses on four essential bases of effective writing - unity, support, coherence and sentence skills. A wide variety of activities and assignments are provided, both structured and creative.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Rhetoric,Grammar,Tu từ học,Ngữ pháp